IMPLEMENTASI SUPERVISI AKADEMIK PENDIDIKAN AGAMA ISLAM UNTUK PENGUATAN KARAKTER MANDIRI SISWA DI SMA NEGERI KESAMBEN JOMBANG - Anis Permata Sari; Nanang Qosim; Dian Kusuma Wardani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Education does not only function as a means of transferring knowledge, but also plays an important role in shaping students’ character, one of which is independence. Islamic Religious Education (IRE) holds a strategic position in instilling values of independence through meaningful learning processes. In this context, academic supervision becomes an essential instrument to improve the quality of IRE learning so that character values can be optimally integrated. This study aims to analyze the implementation of academic supervision in Islamic Religious Education in strengthening students’ independent character at SMA Negeri Kesamben, the role of IRE academic supervision in fostering students’ independent character, as well as the supporting and inhibiting factors in its implementation. This study employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, documentation, and questionnaires. The research subjects included the vice principal for curriculum affairs, Islamic Religious Education teachers, and students of SMA Negeri Kesamben. Data analysis was conducted through data collection, data reduction, data display, and conclusion drawing, while data validity was ensured through credibility, transferability, dependability, and confirmability tests. The results show that IRE academic supervision is implemented through the stages of planning, implementation, and evaluation of learning. Academic supervision plays a role in guiding IRE teachers to integrate independent character values into the learning process. However, its implementation has not been fully optimal due to time constraints, teachers’ workload, and limited understanding of character-based IRE learning. Therefore, IRE academic supervision needs to be carried out in a coaching, reflective, and continuous manner so that the strengthening of students’ independent character can be achieved optimally.